2013
DOI: 10.1002/adfm.201301998
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Dispersible, Ligand‐Free, and Extra‐Small (<10 nm) Titania Nanoparticles: Control Over Primary, Secondary, and Tertiary Agglomeration Through a Modified “Non‐Aqueous” Route

Abstract: Non‐aqueous routes to inorganic nanoparticles are supposedly based on the absence of water; here, this view is partially challenged, showing that the presence of water (or moisture) is probably necessary, and is surely useful to achieve a precise control over the growth/aggregation phenomena leading to titanium dioxide nanoparticles. This study is focused on the preparation of size‐controlled and ligand‐free titania (anatase) nanoparticles in water dispersion. This is achieved through a three‐step process: 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…33,34 Indeed, combining non-aqueous solvents with acidic anions has proved key in the formation of microspheres in such MW syntheses without the need of templating agents. [35][36][37] Commercial MW reactors equipped with pressure sensors and capable of controlling the reaction temperature through incident MW power have been successfully employed for MW solvothermal synthesis. 31,[37][38][39] FMS synthesis differs from this approach, applying constant MW power and exploiting the variation in pressure as the reaction proceeds.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Indeed, combining non-aqueous solvents with acidic anions has proved key in the formation of microspheres in such MW syntheses without the need of templating agents. [35][36][37] Commercial MW reactors equipped with pressure sensors and capable of controlling the reaction temperature through incident MW power have been successfully employed for MW solvothermal synthesis. 31,[37][38][39] FMS synthesis differs from this approach, applying constant MW power and exploiting the variation in pressure as the reaction proceeds.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study on the formation and agglomeration of titania nanoparticles by hydrolysis of various titanium alkoxide precursors in benzyl alcohol, Cadman et al showed that the presence of water promotes the aggregation as well as agglomeration behavior of the formed primary nanoparticles . Cadman concluded that −OH groups present on the particle surface after the addition of water eventually cause a reaction-limited agglomeration of the formed nanoparticles and the formation of fractal structures.…”
Section: Resultsmentioning
confidence: 99%
“…56 Penn also stated that surface-bound ligands play a crucial role as they can passivate crystal faces and prevent particles from aligning, which leads to randomly oriented aggregates. The cubic shape of the nanoparticles and the high specific surface energy of the crystal facets favor oriented aggregation, but the chemisorbed organic ligands hinder particles from aligning their crystal planes during aggregation, 3,57 resulting in randomly oriented structures, as illustrated in Figure 5b. We determined the amount of chemisorbed ligands on the nanoparticle surface (Figure S5, Supporting Information) via thermogravimetric analysis and found that the amount of ligands decreases over the course of the synthesis from 32 to 8 wt %, which is in good accordance with the findings by Penn and the observed structures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, only a few routes involving only aprotic reactions are strictly non‐hydrolytic or non‐aqueous [3, 7] . The presence of water in the reaction medium can impact not only the mechanism of formation of the oxo bridges, but also the structure, surface chemistry, morphology or texture of the final nanomaterials [5, 7, 8] . However, there have been very few attempts at quantifying the water in NHSG reactions, and studies comparing water formation in different NHSG routes for a given oxide are lacking.…”
Section: Introductionmentioning
confidence: 99%